Challenges and experiences faced by social workers working with children exposed to abuse and neglect - Tumwesigye, Keneth (Open Science Journal, 2021)
Child abuse and neglect are the most disturbing problems in the field of child welfare. In the area of child welfare, all over the world, it is common social workers engaged with children such as psychologists; nurses and pediatrician are often affected while carrying out their respective duties. The study is intended to explore the dynamic problems such social workers experience in their line of duty. The issue of social workers engaging with children exposed to child abuse and neglect require much attention and it has to be addressed in line with the child protection system. The child protection system is one of the frameworks of the whole child welfare which provide social services to children exposed to abuse and neglect. In the field of child welfare, different social workers for example pediatricians, psychologists etc work together in assessing children in relation to abuse and neglect. Therefore, this study showcases the need for supportive practice for social workers in the field of child protection to work together. Key Words: Child protection, Social worker, Child abuse and neglect,